Associations of specific postoperative complications with costs after radical cystectomy. (16th November 2017) - Mossanen, Matthew; Krasnow, Ross E.; Lipsitz, Stuart R; Preston, Mark A.; Kibel, Adam S.; Ha, Albert; Gore, John L.; Smith, Angela B.; Leow, Jeffrey J.; Trinh, Quoc‐Dien; Chang, Steven L.
Abstract : Objective: To quantify the financial impact of complications after radical cystectomy (RC) and their associations with respective 90‐day costs, as RC is a morbid surgery plagued by complications and the expenditure attributed to specific complications after RC is not well characterised. Patients and Methods: We used the Premier Hospital Database (Premier Inc., Charlotte, NC, USA) to identify 9 137 RC patients (weighted population of 57 553) from 360 hospitals between 2003 and 2013. Complications were categorised according to Agency for Healthcare Research and Quality Clinical Classifications. Patients with and without complications were compared, and multivariable analysis was performed. Results: An index complication increased costs by $9 262 (95% confidence interval [CI] 8 300–10 223) and a readmission complication increased costs by $20 697 (95% CI 18 735–22 660). The four most costly index complications (descending order) were venous thromboembolism (VTE), infection, wound and soft tissue complications, and pulmonary complications ( P < 0.001, vs no complication). A complication increased length of stay by 4 days (95% CI 3.6–4.3). One in five patients were readmitted in 90 days and the four costliest readmission complications (descending order) were pulmonary, bleeding, VTE, and gastrointestinal complications ( P < 0.001, vs no complication). Readmitted patients had multiple complications upon readmission (median of 3, interquartile range 2–4). On multivariable analysis, more comorbidities, longer surgery (>6 h), transfusions of >3 units, and teaching hospitals were associated with higher costs ( P < 0.05), whilst high‐volume surgeons and shorter surgeries (<4 h) were associated with lower costs ( P < 0.05). Conclusions: Complications after RC increase index and readmission costs for hospitals, and can be categorised based on magnitude. Future initiatives in RC may also consider costs of complications when establishing quality improvement priorities for patients, providers, or policymakers.